2012
DOI: 10.1021/ac302024y
|View full text |Cite
|
Sign up to set email alerts
|

Online Characterization of Particles and Gases with an Ambient Electrospray Ionization Source

Abstract: Methods for online characterization and quantification of gas- and particle-phase species greatly facilitate the study of aerosol particle formation and reaction mechanisms. An online method for aerosol analysis has been developed by altering a conventional electrospray ionization mass spectrometer to direct the aerosol flow through the nebulizing gas inlet. Interaction between the aerosol and electrospray droplets produces ions that are subsequently analyzed by MS or MS/MS with a quadrupole ion trap mass anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 22 publications
1
42
0
Order By: Relevance
“…One approach may be to vaporize the particle not with a heated platform, but with an infrared laser, possibly followed by a separate gas-phase ion source (as in Warschat et al, 2015;Westphall et al, 2008;or Zelenyuk et al, 2009). Alternately, an electrospray-type scheme may be used, such as delivering the particle onto a paper spray source (as in Jacobs et al, 2017), ionizing via an interaction between the particle and a spray of ions (e.g., as in Doezema et al, 2012;Gallimore and Kalberer, 2013;or Horan et al, 2012), or by producing a spray directly from the particle when dropped onto a charged needle tip (as in Tracey et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…One approach may be to vaporize the particle not with a heated platform, but with an infrared laser, possibly followed by a separate gas-phase ion source (as in Warschat et al, 2015;Westphall et al, 2008;or Zelenyuk et al, 2009). Alternately, an electrospray-type scheme may be used, such as delivering the particle onto a paper spray source (as in Jacobs et al, 2017), ionizing via an interaction between the particle and a spray of ions (e.g., as in Doezema et al, 2012;Gallimore and Kalberer, 2013;or Horan et al, 2012), or by producing a spray directly from the particle when dropped onto a charged needle tip (as in Tracey et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possibility is that offline collection and analysis introduces positive artefacts to the nanoESI(−)-MS spectrum, such as via additional reaction on the substrate. Horan et al (2012) found that the relative abundance of oligomers was also higher in filter samples than their online AESI method, which was attributed to a negative filter sampling artefact -the evaporation of semi-volatile material (predominantly monomers) during collection. However, the overall Figure 5.…”
Section: Comparison Of Online Eesi(−) and Offline Nanoesi(−) Mass Spementioning
confidence: 97%
“…However, a number of studies have detected gas-phase species using an electrospray source -e.g. Horan et al (2012), Wu et al (2000) and Zhao et al (2017a). The ion source design and operating parameters appear important in determining the ionisation efficiency and mechanism (uptake into droplets or gas-phase chemical ionisation).…”
Section: Time Series Of Individual Particle-phase Ionsmentioning
confidence: 99%
See 1 more Smart Citation
“…EESI is a soft ionization technique, which in positive ion mode predominantly forms [M + H] + ions. The analyte ion signal intensity is dependent on the analyte solubility, concentration and proton affinity (in positive ion mode), assuming that the experimental configuration is constant …”
Section: Introductionmentioning
confidence: 99%